Metal binding selectivity of an N-terminally free multihistidine peptide HAVAHHH-NH2. (11th December 2018) - Balogh, Bettina Diána; Bihari, Zsolt; Buglyó, Péter; Csire, Gizella; Kerekes, Zsuzsanna; Lukács, Márton; Sóvágó, Imre; Várnagy, Katalin
Abstract : For NH2 -HAVAHHH-NH2 peptide the coordination to internal histidines is preferred for copper(ii ), while it is the opposite for nickel(ii ). Abstract : Copper(ii ), nickel(ii ), zinc(ii ) and organometallic ruthenium(ii ) ([(η 6 - p -cym)Ru(H2 O)3 ] 2+ ) complexes of an N-terminally free heptapeptide containing four histidyl residues (NH2 -HAVAHHH-NH2 ) have been studied by potentiometric and various spectroscopic techniques (UV-vis, CD, NMR and ESI-MS). The data revealed a significant selectivity in the metal binding ability of this ligand. Histamine-like coordination of the amino terminus is the primary binding mode for all metal ions but the internal histidyl residues can also contribute to the overall stability of the complexes. Copper(ii ) and nickel(ii ) ions are able to induce the deprotonation and coordination of the amide functions both at the amino terminus and around the internal histidyl sites, resulting in the co-existence of various coordination isomers or the formation of dinuclear complexes in the presence of excess of metal ions.